Analysis of circulating tumour DNA to monitor disease burden following colorectal cancer surgery. Issue 4 (4th February 2015) - Reinert, Thomas; Schøler, Lone V; Thomsen, Rune; Tobiasen, Heidi; Vang, Søren; Nordentoft, Iver; Lamy, Philippe; Kannerup, Anne-Sofie; Mortensen, Frank V; Stribolt, Katrine; Hamilton-Dutoit, Stephen; Nielsen, Hans J; et al.
Abstract : Objective: To develop an affordable and robust pipeline for selection of patient-specific somatic structural variants (SSVs) being informative about radicality of the primary resection, response to adjuvant therapy, incipient recurrence and response to treatment performed in relation to diagnosis of recurrence. Design: We have established efficient procedures for identification of SSVs by next-generation sequencing and subsequent quantification of 3–6 SSVs in plasma. The consequence of intratumour heterogeneity on our approach was assessed. The level of circulating tumour DNA (ctDNA) was quantified in 151 serial plasma samples from six relapsing and five non-relapsing colorectal cancer (CRC) patients by droplet digital PCR, and correlated to clinical findings. Results: Up to six personalised assays were designed for each patient. Our approach enabled efficient temporal assessment of disease status, response to surgical and oncological intervention, and early detection of incipient recurrence. Our approach provided 2–15 (mean 10) months' lead time on detection of metastatic recurrence compared to conventional follow-up. The sensitivity and specificity of the SSVs in terms of detecting postsurgery relapse were 100%. Conclusions: We show that assessment of ctDNA is a non-invasive, exquisitely specific and highly sensitive approach for monitoring disease load, which has the potential to provide clinically relevant lead times compared with conventional methods. Furthermore, we provide a low-coverage protocol optimised for identifying SSVs with excellent correlation between SSVs identified in tumours and matched metastases. Application of ctDNA analysis has the potential to change clinical practice in the management of CRC.